2002
DOI: 10.1128/aac.46.9.3096-3100.2002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Echinocandin Caspofungin on Expression of Candida albicans Secretory Aspartyl Proteinases and Phospholipase In Vitro

Abstract: Although the echinocandin caspofungin primarily inhibits the synthesis of cell wall 1,3-␤-D-glucan, its fungicidal activity could also potentially perturb the expression of virulence factors involved in the ability of Candida albicans to cause infection. Expression of the C. albicans secretory aspartyl proteinase (SAP) and phospholipase B (PLB) virulence genes was determined by reverse transcription-PCR after the addition of caspofungin to cells grown for 15 h in Sabouraud dextrose broth. In cells that remaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 50 publications
2
24
0
Order By: Relevance
“…This result may be due to Caspofungin's ability to increase amphotericin B‐induced renal toxicity. Ripeau et al have recently reported that Caspofungin can increase the expression of Candida albicans secretory proteinase 5 28. Secretory proteinases may selectively release active amphotericin B from the ABLC at sites of fungal infection in a similar way as fungal cell‐derived phospholipases32 resulting in more active amphotericin B available to not only cause damage to fungal cells but also to surrounding renal cells.…”
Section: Discussionmentioning
confidence: 99%
“…This result may be due to Caspofungin's ability to increase amphotericin B‐induced renal toxicity. Ripeau et al have recently reported that Caspofungin can increase the expression of Candida albicans secretory proteinase 5 28. Secretory proteinases may selectively release active amphotericin B from the ABLC at sites of fungal infection in a similar way as fungal cell‐derived phospholipases32 resulting in more active amphotericin B available to not only cause damage to fungal cells but also to surrounding renal cells.…”
Section: Discussionmentioning
confidence: 99%
“…The C. albicans isolates from the HIV-positive group that were characterized by higher levels of peptidase activity were also less susceptible to the widely used azole antifungal agents ketoconazole and fluconazole (Ollert et al 1995). C. albicans strains exposed to subinhibitory concentrations of antifungals belonging to the azole, echinocandin, and pyrimidine analog classes showed an elevated activity of Sap2 in the culture filtrates (Wu et al 2000;Ripeau et al 2002). In addition, the expression of SAP2 and activity of the secreted Sap2 gene product was upregulated in fluconazole-exposed yeast cells (Copping et al 2005).…”
Section: Candida Sppmentioning
confidence: 97%
“…CPF (Cancidas Ò , Merck Sharp & Dohme, Whitehouse Station, NJ, USA) is derived from pneumocandin B, which in turn was isolated from the fungus Glarea lozoyensis [62,63]. ANDF (Eraxis Ò , Pfizer, New York, USA) is a semisynthetic product of echinocandin B, which is a fermentation product of the mold A. nidulans.…”
Section: Antifungal Drugs That Target the Fungal Cell Wallmentioning
confidence: 99%